Genocidal sexual assault on women and the role of culture in the rehabilitation process: Experiences from working with Yazidi women in Turkey - Yüksel, Sahika; Saner, Suzan; Basterzi, Ayse Devrim; Oglagu, Zerrin; Bülbül, Israfil (Torture Journal, 2018)
Input abstract